An Active Learning App Development Module for Novices: A Self-Assessment Approach - Binder, Fabio; Gonzatto, Rodrigo; Veloso, Luiz; Mendonça, Vinícius; Reinehr, Sheila; Malucelli, Andreia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
This paper is part of continuous research in an experimental educational project that started in 2013, whose methodology used was mainly action research. It is proposed and analyzed a module, offered in 2019, for teaching mobile applications development with a focus on Swift Playground and Xcode programming and UX/UI design. The audience are students beginning in programming and students beginning in design using the Challenge Based Learning active methodology. The module, called Crash Challenge, lasted eight weeks in two different classes, one with 25 students and the other with 24 students, with 44 applications published and several self-assessment touchpoints. The scope of the paper involves the perception of the programming learning of the subset of 23 non-programmer students. During the module, we collected data through surveys, feedbacks and self-reflection texts. The surveys allowed a quantitative analysis of a proposed self-perception and the texts of self-reflection investigated by a qualitative analysis of thematic networks to identify the perception of learning. The findings may be used as best practices to help the creation or improvement of app development courses in order to train students from areas not directly related to programming, and enhance self-assessment and self-pacing as learning practices in this area.